Predictive value of myocardial strain on myocardial infarction size by cardiac magnetic resonance imaging in ST-segment elevation myocardial infarction with preserved left ventricular ejection fraction - Wang, Qiang; Wang, Jian; Ma, Yingjie; Wang, Peng; Li, Yang; Tian, Jing; Yue, Xiuzheng; Su, Guohai; Li, Bin (Frontiers in Pharmacology, 2022)
Background: The correlation between myocardial strain and infraction size by cardiac magnetic resonance imaging in ST-segment elevation myocardial infarction (STEMI) with preserved left ventricular ejection fraction (LVEF) is not clear. Objective: To investigate the correlation between myocardial strain and myocardial infarction size in patients of acute STEMI with preserved LVEF. Materials and Methods: A retrospective study was conducted to assess 31 patients with acute ST-segment elevation myocardial infarction (STEMI)after primary percutaneous coronary intervention (PCI) who received cardiac magnetic resonance (CMR) imaging during hospitalization at the Central Hospital of Shandong First Medical University from 2019 to 2022 and whose echocardiography indicated preserved LVEF (LVEF≥50%). The control group consisted of 21 healthy adults who underwent CMR during the same period. We compared the CMR characteristics, global and segmental strain between the two groups. Furthermore, the correlation between the global strain and the segmental strain of the left ventricle and late gadolinium enhancement (LGE) were evaluated. Results: Compared with healthy controls, the left ventricular ejection fraction (LVEF) of STEMI patients with preserved LVEF was significantly decreased (p < 0.05). Moreover, the global radial strain (GRS) (24.09% [IQR:17.88–29.60%] vs. 39.56% [IQR:29.19–42.20%], p < 0.05), global circumferential strain (GCS) [−14.66% (IQR: 17.91–11.56%) vs. −19.26% (IQR: 21.03–17.73%), p < 0.05], and global longitudinal strains (GLS) (−8.88 ± 2.25% vs. −13.46 ± 2.63%, p < 0.05) were damaged in patients. Furthermore, GCS and GLS were associated with LGE size (%left ventricle) (GCS: r = 0.58, p < 0.05; GLS: r = 0.37, p < 0.05). In the multivariate model, we found that LGE size was significantly associated with GCS (β coefficient = 2.110, p = 0.016) but was not associated with GLS (β coefficient = −0.102, p = 0.900) and LVEF (β coefficient = 0.227, p = 0.354). The receiver operating characteristic (ROC) results showed that GCS emerged as the strongest LGE size (LGE >25%) prognosticator among strain parameters (AUC: 0.836 [95% CI, 0.692—0.981], sensitivity: 91%, specificity: 80%) and was significantly better (p = 0.001) than GLS [AUC: 0.761 (95% CI, 0.583—0.939), sensitivity: 64%, specificity: 85%] and LVEF [AUC: 0.673 (95% CI, 0.469—0.877), sensitivity: 73%, specificity: 70%]. Conclusion: Among STEMI patients with preserved LVEF after PCI, CMR-FT-derived GCS had superior diagnostic accuracy than GLS and LVEF in predicting myocardial infarction size.